Assessment of the Quality of Obstetric Services From the Perspective of Maternity Patients and Service Providers in a Tertiary Care Obstetric Unit in Lithuania - Justina Katinaitė-Vaitkevičienė; Aleksandras Patapas (SAGE Publishing, 2023)
Although largely focused on the patient, the provision of healthcare services is a 2-way process and its success hinges on the interactions between patients and physicians. Given the growing role of subjective, patient-dependent assessment of the quality of care received, which is increasingly influenced by the individual aspects of the interaction between patients and care providers, in addition to the explicitly measurable, objective assessment of the quality of care received based on clinical indicators, quality assessment of services should especially consider and explore the attitudes, needs and dynamics of all the parties involved in the healthcare process. This study was designed to assess the attitudes of maternity patients and healthcare providers towards the quality of obstetric care. A quantitative questionnaire survey was conducted in a tertiary level healthcare facility providing obstetric services in Lithuania. Research findings suggested that maternity patients rate both the technical and functional quality of obstetric services higher than the staff providing it. Midwives and obstetricians-gynaecologists view quality assurance as a complex process, rather than focus solely on quantitative indicators. Since midwives were rated slightly higher than physicians in terms of services they provide, it may be appropriate to ensure and encourage a wider use of midwife-only deliveries in low-risk births. A comprehensive assessment of the quality assurance aspects as viewed by the patients and the staff should be included in the regular quality assessments of healthcare facilities as one of the most informative assessment tools on the service quality.